Prisons as Schools: Inmates' Participation in Vocational and Academic Programs in Chinese Prisons - Zhao, Yunhan (International journal of offender therapy and comparative criminology, 2019)
Although the idea of criminal rehabilitation in China has a long history, research on offender rehabilitation in contemporary China is limited. Although Chinese scholars generally agree that rehabilitation through correctional education helps inmates with social reintegration and reduces recidivism, few have examined factors associated with prisoners' participation in such programs. Building on relevant theory and studies in Western societies, this study examines how Chinese prisoners' participation in vocational and academic programs is associated with a range of push and pull factors. Our research questions are addressed with binary and multinomial logistic regressions based on a unique prisoner data set collected in Zhejiang, China. Results show that some factors found to affect inmate participation in the West failed to demonstrate significant relationships with participation among Chinese prisoners. Furthermore, factors most significantly associated with participation appear to be incarceration related, such as prison visits, prison phone calls, and sentence lengths. We conclude with a discussion of the implications of our results.